Pengaruh Kepemimpinan Kepala Madrasah Terhadap Pembiasaan Berbudaya Religius - Asiroh, Asiroh; Supriatman, Maman; Munawaroh, Mumun (JIEM (Journal of Islamic Education Management), 2020)
The education that parents want for their children today is not only having intellectual intelligence, but also being balanced with spiritual intelligence. So this study aims to determine how much influence the leadership of madrasa leaders on religious cultural habituation in MTs Al-Nur Cirebon City. This type of research is quantitative research. The subjects of this study were students and teachers taken only 38 people by means of the stratified random sampling technique. Data collection techniques were carried out by means of observation, questionnaires with Likert scale models and documentation studies. The validity test was carried out using the construct test technique and the Pearson Product Moment correlation technique. While the reliability test is used by the Alpha method formula. The number of valid items for the madrasah headship variable is 33 items, while the number of valid items for the religious cultural habituation variable is 31 statement items. Prerequisite analysis test uses normality test, linearity test. Then the data are analyzed using a simple linear regression formula. The significance level is set at 5%. Based on the results of calculations and analysis, it was concluded that the magnitude of the influence of madrasa head leadership on religious cultural habituation was relatively low with a correlation coefficient r of 0.390. While the contribution of the influence of madrasa head leadership to religious cultural habituation in MTs Al-Nur Cirebon City was only 15.2%.Â Keywords: Leadership of Madrasah Head, Religious Cultured.